(untitled) - Ethel Tiersky (Englewood Cliffs, New Jersey, 1990)
The book describes and analyzes contemporary lifestyles, provides useful information about history and government for readers planning to take citizenship tests, and teaches advanced vocabulary and idioms that students are likely to encounter on the TOEFL.
Keywords: english language - textbooks for foreign speakers,readers - united states,united states - civilization